1982
DOI: 10.2136/sssaj1982.03615995004600020027x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Accumulation and Toxicity in Leaves in Relation to Zinc Supply

Abstract: The relationship of zinc (Zn) deficiency to phosphorus (P) toxicity was examined in ‘Emerald’ okra [Abelmoschus esculentus (L.) Moench] grown for 21 days (D21) in complete nutrient solution and then transferred to treatments with two levels of P (P1, P2 = 250, 2,000 µM P) and four levels of Zn (Zn1, Zn2, Zn3, Zn4 = 0, 0.25, 1, 2 µM added Zn).No symptoms of “little leaf” or “rosetting” developed in any plants. “Mottle leaf” symptoms developed as chlorotic and necrotic patches in the interveinal areas of the old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
81
2
6

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 0 publications
21
81
2
6
Order By: Relevance
“…Our results, and those of others, support the suggestion by Loneragan et al (1982) that Zn deficiency interferes with the control of ion uptake in a general way. In a companion paper (Welch and Norvell, 1993), we present evidence that Zn plays a role in the maintenance of root cell membranes, as first reported by Welch et al (1982).…”
Section: Zn2+ Activity Required For Optimum Nutrient Accumulation Andsupporting
confidence: 92%
“…Our results, and those of others, support the suggestion by Loneragan et al (1982) that Zn deficiency interferes with the control of ion uptake in a general way. In a companion paper (Welch and Norvell, 1993), we present evidence that Zn plays a role in the maintenance of root cell membranes, as first reported by Welch et al (1982).…”
Section: Zn2+ Activity Required For Optimum Nutrient Accumulation Andsupporting
confidence: 92%
“…It may also be possible to breed lower PA concentrations into the grains of staple crops and the benefits of even marginal reductions in grain PA concentration on Zn bioavailability could be large at population scales (Joy et al 2014). Interestingly, it has been reported that Zn-enriched fertilisers can decrease concentrations of PA in cereal grains while Zn deficiency may lead to increased P uptake and accumulation in plants (Loneragan et al 1982;Erdal et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Citam-se a baixa velocidade de translocação do Zn das raízes para a parte aérea (Souza et al, 2006); o efeito de diluição do Zn na parte aérea, pelo crescimento da planta, em resposta à adição do P (Marinho & Igue, 1972) ou o distúrbio metabólico nas células da planta, provoca do pelo desequilíbrio entre P e Zn (Loneragan et al, 1982). Souza et al (2006) constataram interação negativa entre P e Zn em mudas de cacaueiro, princi palmente nas raízes, o que resultou na redução da translocação de Zn para as folhas.…”
Section: Introductionunclassified
“…Souza et al (2006) constataram interação negativa entre P e Zn em mudas de cacaueiro, princi palmente nas raízes, o que resultou na redução da translocação de Zn para as folhas. Loneragan et al (1982) relataram que a deficiência de Zn estimula não só a taxa de absorção de P pelas raízes como também a translocação de P para a parte aérea. Este estímulo é específico para o Zn, não sendo verificado para outros micronutrientes.…”
Section: Introductionunclassified